Motor Unit Number Estimation and Quantitative EMG : Proceedings of the Second International Symposium on MUNE and QEMG, Snowbird, Utah, USA, 18-20 August 2006 /: Proceedings of the Second International Symposium on MUNE and QEMG, Snowbird, Utah, USA, 18-20 August 2006. (©2009) - Unknown
No abstract available